Effect of Hot Water Pretreatment on the Strength of the Fibre and Heat Insulation Properties - Ab Rahman , Asyraf Adam; Samsudin, Emedya Murniwaty (Recent Trends in Civil Engineering and Built Environment, 2023)
This research aims to demonstrate the use of natural fibres (empty fruit bunch) in the production of fibre cement boards. The effects of different hot water soaking temperatures on the fibre performance according to different strand-diameter-range were determined by tensile strength and the treated fibre are used in the cement board fibre composite fabrication and tested for its thermal conductivity. Temperatures used during pretreated are 50oC, 60oC, 70oC, 80oC and 90oC with untreated fibre as a control sample with soaking durations for 2 hours. Cement: fibre ratio used in the fabrication of the cement board is 3: 1 while the size of cement board for thermal testing is prepared as 150 mm x 150 mm x 12 mm. To investigate the effects of pre-treatment to the strand durability, tensile strength testing is done using UTM Instron Machine. Results on thermal conductivity showed that higher temperature used during fibre immersion affects the speed of heat penetrates into the EFB-CB material with temperatures of 80oC and 90oC are found to be the optimum temperatures with good thermal resistivity. As for the tensile strength result, it was observed that diameter and pretreatment temperature greatly affect the strength of the fiber. The strongest strand is the one with diameter range between 15 mm to 20 mm treated using temperatures of 60°C achieved 869 MPa. As the strand goes thicker range, the fibre are found to be weaker to restrain higher tensile load. Of all, 60oC to 70oC are found to be the optimum temperatures for hot water treatment that result in higher tensile strength. Hence, it is possible to conclude that hot water pretreatment has a substantial impact on the thermal conductivity of EFB cement board and the tensile strength of a single fibre strand.